Smart Count Of Vehicle Loading Prototype pada Kapal Berdasarkan Berat Kendaraaan Menggunakan ESP32 - Surono Surono; Edi Kurniawan; Akhmad Khasan Gupron (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The primary focus of this research was to create a Smart Count of Vehicle Loading Prototype for ships, with an emphasis on monitoring and tallying vehicles boarding and disembarking from ships based on their weight. Microcontrollers, such as the ESP32, were utilized for the counting process and to determine if the ship's cargo weight exceeded its maximum capacity. The main objective was to prevent overloading on ships, which could lead to accidents during voyages or while vehicles were being loaded onto the ship. To achieve this goal, weight and distance sensors were installed on the ship and controlled by the microcontroller, allowing for accurate monitoring of the quantity and categories of vehicles being loaded. After designing and testing this prototype device, it has become a new technological innovation that makes monitoring the weight and quantity of cargo on ships easier and more efficient. This is supported by the fact that each sensor's readings can work well with an average error rate below 2%. Additionally, the maximum communication range between the Blynk IoT application and the ship system can reach up to 20 meters.